STUDENT CRITICAL THINKING IN USING TIKTOK TO FIND RELIABLE RESOURCES FOR LEARNING ENGLISH - Amaliani, Nifah; Adhitya, Novandy; Kusumayanthi, Susie (English Education Department of STKIP Pasundan, 2026)
This paper discusses college students’ critical thinking in using TikTok to find reliable resources for learning English. Previous researchers had worked on how TikTok can improve the student's understanding in learning English and how to engage the skill in English language. The focus on this study is on how students locate and identify TikTok video content that may be used as a source or educational material from a reliable source or content creator who is an expert in the subject. The purpose in this study is how the way student can find reliable resources for learning English. The research participants in this study conducted 3 students from higher education. The method of the paper is using a qualitative method with narrative inquiry approached. Based on the data TikTok video can help students to learn English, but in determining whether it is reliable or not, it needs to be confirmed by doing research again on various platforms. Because there is no stipulation that only certified people can share information, also anyone can give information without know that material is fact or hoax and participants choose it based on the fact that the account is from a native speaker, English course, and English teacher.